Actualization of evidence-based nursing in primary, specialized, and social care settings—A cross-sectional survey - Hamari, Lotta (WILEY, 2025)
Background: Basing practice on evidence is a widely acknowledged requirement for nursing, but shortcomings still exist. An increased understanding of the actualization of evidence-based nursing (EBN) across different nursing contexts is needed to develop better support for EBN and promote uniform high-quality nursing.
Aims: The aim of this study was to compare the actualization of EBN in different organizational contexts in Finland.
Methods: Data for this survey were collected in 2021. The actualization of EBN in primary, specialized, and social care organizations was evaluated with the Actualization of Evidence-Based Nursing instrument, nurses' version, which focuses on individual and organizational-level EBN support structures. Differences between (1) specialized and primary healthcare, and (2) different nursing practice settings were tested with Welch's two sample t-test, the Kruskal-Wallis rank sum test, and the Wilcoxon rank sum test.
Results: Based on nurse (n = 1020) evaluations, those working in specialized healthcare hold more positive attitudes toward EBN (p = .021) and evaluated their organization's methods for monitoring and evaluating nursing practices (p = .004) more positively than those working in primary healthcare. Regarding different nursing practice settings (n = 1241), the most positive results were observed within preventive healthcare where nurses evaluated their attitudes toward EBN, EBN competence, and personal evidence-based practices more positively compared to other nursing practice settings. The results were parallel regarding several organizational structures for EBN. Positive results were also observed within somatic units at university hospitals, and most negative results were within institutional care settings, health centers, and home care settings.
Linking Evidence to Action: There is a need for targeted support to strengthen EBN across different organizational contexts, with special attention to those contexts where nursing professionals with lower education levels work. Future research needs to focus on further analyzing the organizational differences and what can be learned, especially from preventive healthcare but also somatic units at university hospitals.